Prospective study of postoperative whole breast radiotherapy for Japanese large-breasted women: a clinical and dosimetric comparisons between supine and prone positions and a dose measurement using a breast phantom. Issue 1 (December 2016) - Takahashi, Kana; Morota, Madoka; Kagami, Yoshikazu; Okamoto, Hiroyuki; Sekii, Shuhei; Inaba, Koji; Murakami, Naoya; Igaki, Hiroshi; Ito, Yoshinori; Uno, Takashi; Itami, Jun
Abstract Background This prospective study aimed to compare dose volume histograms (DVH) of the breasts and organs at risk (OARs) of whole breast radiotherapy in the supine and prone positions, and frequency and severity of acute and late toxicities were analyzed. Methods Early-stage breast cancer patients with large breasts (Japanese bra size C or larger, or the widest measurements of the bust ≥ 95 cm) undergoing partial mastectomy participated in this study. CT-based treatment plans were made in each position, and various dosimetric parameters for the breast and OARs were calculated to compare the supine and prone radiotherapy plans. The actual treatment was delivered in the position regarded as better. Results From 2009 to 2010, 22 patients were prospectively accrued. Median follow-up period was 58 months. The homogeneity index and lung doses were significantly lower in the prone position (P  = 0.008, P  < 0.0001 andP  < 0.0001, respectively). Cardiac dose showed no significant differences between two positions. By comparing two plans, the prone position was chosen in 77 % of the patients. In the prone position, ≥ grade 2 acute dermatitis were seen in 47 % of patients treated, whereas 20 % of the patients treated in the supine position had grade 2 and no cases of grade 3, although without a statistical significance of the rates of ≥ grade 2 acute dermatitis between the two positions (P  = 0.28). The actual dose measurement using a breast phantom revealed significantly higher surface dose of the breast treated in the prone position than that in the supine position. Conclusions Breast irradiation in the prone position improves PTV homogeneity and lowers doses to the OARs in the Japanese large-breast patients. However meticulous positioning of the breast in the prone board avoiding the bolus effect is necessary to prevent acute dermatitis.